Ventriculography Modality in Detection and Evaluation of Cardiotoxicity in Breast Cancer Patients Receiving Chemotherapy: A Literature Review (National Cancer Center - Dharmais Cancer Hospital, 2022)
Background: Ventriculography or Multigated Acquisition Scanning (MUGA) has been the gold standard for baseline and serial assessment of Left Ventricular Ejection Fraction (LVEF) for cardiotoxicity since 1970. However, several modalities have been proposed to substitute Ventriculography. This study aimed to find out whether Ventriculography can still be considered the gold standard to monitor and detect cardiotoxicity before, during, and after administration of the chemotherapy and compare Ventriculography with Cardiac Magnetic Resonance (CMR) and Echocardiography (Echo).Methods: A literature review was done by searching original literature with keyword combinations on PubMed, Cochrane, and ClinicalKey in the past five years (2016–2021) with language restrictions only in English. Of 1,381 pieces of literature, five pieces are included to review in this study. Results: Ventriculography has high sensitivity and specificity in monitoring and detecting cardiotoxicity. Other modalities are CMR and Echo. CMR is more accurate although it is costly whilst Echo has high interobserver variability. Ventriculography and CMR have not shown interchangeable results. The literature also shows that Ventriculography could evaluate cardiotoxicity by assessing diastolic function. Conclusions: Ventriculography can still be used as the gold standard for monitoring cardiac function and detecting cardiotoxicity at an affordable price and with acceptable side effects. It recommends choosing only one modality for serial monitoring due to not interchangeable results among modalities